Ludwig von Mises as currency school free banker - Salerno, Joseph T. (REVISTA PROCESOS DE MERCADO, 2012)
The centennial of the publication of the first German edition of Ludwig von Mises’s The Theory of Money and Credit offers an excellent opportunity to reconsider a long-standing controversy within modern Austrian economics. This revolves around the question of whether Ludwig von Mises favored 100-percent gold reserve banking imposed by law or free banking based on gold as the ideal monetary system. In this paper, I suggest that this debate is fundamentally misfocused and conflates means and ends. I argue that Mises advocated free banking as the most suitable means for achieving the goal of suppressing the issue of fiduciary media, in the form of bank notes and demand deposits. This goal was first enunciated by the nineteenth-century British currency school and embodied in its famous «currency principle.» My thesis is that Mises was a proponent of both the currency principle and free banking and that he viewed the latter as the indispensable means to regulate the behavior of the money supply according to the former. In defending this thesis, I seek to reframe the debate on Mises’s monetary views in a more meaningful way and to contribute to its resolution. Key words: Mises, Currency School, Free Banking, Currency Principle, Monetary Equilibrium. JEL Classification: B31, B53, E42, E52. Resumen: El centenario de la publicación de la primera edición alemana de The Theory of Money and Credit de Ludwig von Mises, ofrece una exce-lente oportunidad para reconsiderar una controversia duradera dentro de la economía austriaca moderna. Ésta gira en torno a la cuestión de si Ludwig von Mises apoyó una banca de reserva en oro del 100% impues-ta por ley o una banca libre basada en el oro como su sistema monetario ideal. En este trabajo, sugiero que este debate está fundamentalmente mal enfocado y confunde medios y fines. Sostengo que Mises defendió un siste-ma de banca libre como el medio más adecuado para lograr el objetivo de suprimir la emisión de dinero fiduciario en forma de billetes bancarios y depósitos a la vista. Este objetivo fue inicialmente enunciado por la Escue-la Monetaria del siglo XIX e incorporado en su famoso «principio mone-tario.» Mi tesis es que Mises fue proponente del principio monetario y de la banca libre, y que observó a esta última como el medio indispensable para regular el comportamiento de la oferta monetaria conforme al prime-ro. En la defensa de esta tesis, trato de replantear el debate sobre las ideas monetarias de Mises de una forma más relevante y contribuir de este modo a su resolución. Palabras clave: Mises, Escuela Monetaria, Banca Libre, Principio Monetario, Equilibrio Monetario. Clasificación JEL: B31, B53, E42, E52.